BELAJAR DARI KEJADIAN BENCANA ALAM SEPANJANG TAHUN 2021 - Sulistya, Widada (Jurnal Widya Climago, 2022)
The studies have shown that there has been a tendency to increase hydrometeorological disasters in Indonesia caused by extreme weather, the causes of extreme weather is the La Nina. The La Nina period is understood to cause a positive rainfall anomaly, which means that the rainfall is higher than normal. In this study, we used data from the BNPB for the year 2021. Continuation in this study uses discryptive analysis methods, i.e. methods of analysis based on statistical data. During the year 2021 has occurred 1727 events of hydrometeorological disaster. Hydrometeorological disasters are the most common (96%), with the rest being geological and hydroceanological. Floods are the most frequent hydrometeorological disasters and cause the most casualties. During the year 2021 has been recorded as many 242 people victims of flooding. The victims of the hydrometeorological disaster is causes of the insufficient capacity of the community to prepare for the threat of the horometeorologic disaster. There is a need for educational and illiterate efforts on hatred for the community to increase the capacity of preparedness to face the threat of hydrometeorological disasters.